Tricuspid Valve Replacement, Permanent Pacemaker Insertion, and Orthotopic Liver Transplantation in a Patient with Decompensated Chronic Liver Disease Complicated by Severe Tricuspid Regurgitation - Anuhya Rambhatla; G. V. Prem Kumar; Shakti Swaroop; Govindu Banoth; Sindhuja Kayati; Balachandran Palat (Indian Journal of Transplantation)
This case report delineates the comprehensive management of a 61-year-old female presenting with decompensated chronic liver disease, severe tricuspid regurgitation, and mild pulmonary arterial hypertension necessitating liver transplantation (LT). The patient underwent tricuspid valve replacement which was complicated with complete heart block for which pacemaker insertion was done followed by LT. A multidisciplinary approach was crucial in ensuring optimal preoperative care and successful outcomes.